2013
DOI: 10.1128/jcm.01737-13
|View full text |Cite
|
Sign up to set email alerts
|

Point-Counterpoint: β- d -Glucan Testing Is Important for Diagnosis of Invasive Fungal Infections

Abstract: POINT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
134
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(137 citation statements)
references
References 34 publications
0
134
1
2
Order By: Relevance
“…␤-Glucan is stable, and slow clearance from the CSF compartment may occur in coccidioidal meningitis. The lack of correlation with the organism burden and response to therapy is in contrast with the experience with Candida meningitis in rabbits (19), cryptococcal meningitis in humans (16), pediatric central nervous system infections (12), and serum ␤-glucan results in other clinical mycoses (15). However, the serum ␤-glucan value and even its early kinetics did not correlate with outcomes in other mycoses in some studies (20).…”
Section: Discussioncontrasting
confidence: 42%
“…␤-Glucan is stable, and slow clearance from the CSF compartment may occur in coccidioidal meningitis. The lack of correlation with the organism burden and response to therapy is in contrast with the experience with Candida meningitis in rabbits (19), cryptococcal meningitis in humans (16), pediatric central nervous system infections (12), and serum ␤-glucan results in other clinical mycoses (15). However, the serum ␤-glucan value and even its early kinetics did not correlate with outcomes in other mycoses in some studies (20).…”
Section: Discussioncontrasting
confidence: 42%
“…This low sensitivity might indicate a problem with false-negative results, due to the heterogeneity of the 24 IFD cases diagnosed (14 cases of invasive candidiasis, 5 of aspergillosis, 3 of cryptococcal meningitis, and 1 of Pneumocystis pneumonia) over a period of 1 year. Although the infections detected by the BG assay include all fungal infections, BG levels will usually be low or absent in patients with Cryptococcus infections (24). In order to estimate the sensitivity of the BG assay in our study, we used the samples obtained after the first week and only found six episodes of invasive candidiasis without any other invasive fungal infection (IFI).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical signs and symptoms of IFD are often nonspecific; hence, screening strategies with non-culture-based assays, such as BDG screening, can be useful for early diagnosis of infection (12). BDG is included as a mycological criterion in the revised definitions for IFD by the EORTC/MSG consensus group (4), and BDG testing has a BII recommendation for adults with hematological malignancies and HSCT recipients (13).…”
Section: Discussionmentioning
confidence: 99%